INFLUENCE OF FUNCTIONAL PLAY MATERIALS ON SOCIAL DEVELOPMENT OF PRESCHOOL CHILDREN IN KEERA ZONE, NYAMAIYA DIVISION NYAMIRA COUNTY, KENYA - Edwin M. Mecha,; Godfrey Ayaga, (IJRDO- Journal of Educational Research, 2020)
The need to improve child’s development and learning through plays is a substance of global anxiety for all preprimary school stakeholders. Thus, the purpose of the study was to assess the influence of forms of play materials on social development of preschool children in Keera Zone, Nyamaiya Division Nyamira County, Kenya. The study adopted the Social Interaction Learning Theory,  Social Learning Theory and Social cultural approach.  The information provided by this research will benefit policymakers, community members and academicians. The study applied mixed methods approach and Concurrent triangulation design where quantitative and qualitative and quantitative data were collected at the same time. The target population was 128 respondents comprised of 26 head teachers and 102 teachers. The study employed census inquiry by using all the 26 head teachers and 102 teachers of preschool. The researcher collected data using questionnaires and interview guides.  The instruments were piloted to establish validity, reliability, credibility and dependability. Validity was arrived at through expert judgment, reliability of the instrument was determined using split half technique where Cronbach alpha coefficients of 0.749, 0.768 and 0.726 were obtained. Credibility of the research instrument was ascertained during the pilot study to be carried by the on ten sampled ECDE learners and two teachers while dependability of the research instruments was ascertained by use of observation methods on sampled children. Data collected was analyzed qualitatively and quantitatively. Qualitative data was analyzed using themes and presented in narrative form. Quantitative data was analyzed descriptively then presented in tables and pie charts while inferential statistics were presented in coefficient correlation. The study established that availability of functional play materials, teachers’ approaches in utilization of play materials and frequency of learners’ participation in play activities determines social development of preschool children. It was, therefore, recommended that the schools should provide more varieties of play material to pre-school children as this is likely to improve their social development and The Ministry of Education should allow more time for outdoor and play activities in the pre-school timetable so as to expose the children to more play.